فاعليَّة برْنامج تعليمي قائم على نظرية الذات الإبداعية في تنمية مهارات تحليل النصوص الأدبية لدى طلاب الصف الخامس الأدبي (Journal of the College of Basic Education, 2025)
This research aims to build an educational program based on the theory of the creative self in developing the skills of analyzing literary texts among fifth-grade literary students, and to identify the effectiveness of the educational program. The researchers followed the procedures of the descriptive approach in construction and the procedures of the experimental approach in experimentation, as the researchers prepared an educational program and to verify the research procedures; The researchers adopted an experimental design. The research community consisted of (858) students, and they randomly selected the sample, with (30) students, the experimental group (31) students for. The researchers rewarded the students of the two research groups with chronological age, a linguistic ability test, parents' academic achievement, and a test of literary text analysis skills. The researchers prepared a test that measures the skills of analyzing literary texts, which included (35) paragraphs. They confirmed the validity and reliability of the test, and its psychometric properties. After applying it, they used the SPSS program. The researchers concluded that the students of the experimental group outperformed the students of the control group in the test of literary text analysis skills, as well as the effectiveness of the educational program. The researchers concluded that the educational program proved effective in developing the skills of analyzing literary texts among fifth-grade literary students, because it included new and interesting methods of learning. They recommended the need to focus on creative self-learning and encourage students to participate effectively. They suggested conducting a similar study to identify the effectiveness of the educational program based on the theory of the creative self in developing literary appreciation skills among fifth-grade literary students